The Animation of Cinema - Alan Cholodenko (Semiotic Review)
This essay (originally published in THE SEMIOTIC REVIEW OF BOOKS VOLUME 18.2 2008, republished here with permission) seeks to resurrect the name, work and extraordinary achievements of the most significant pioneering film animator at best marginalized, at worst effaced, by English language Film Studies and Animation Studies. Even the outstanding animation scholar Donald Crafton, in his canonical text Before Mickey: The Animated Film 1898-1928, treats Emile Reynaud as not an animator, situating the advent of animation in 1898, six years after Reynaud began to present his Théâtre Optique at the Musée Grévin in Paris to what would eventually be 500,000 spectators, including arguably the Lumière Bros, as monographs in French on Reynaud propose. The essay continues the author’s work on the theorising of animation begun with his Introduction to and essay “Who Framed Roger Rabbit, or The Framing of Animation” in The Illusion of Life: Essays on Animation, the world’s first anthology of scholarly essays theorising animation and from “poststructuralist” and “postmodernist” perspectives, published by Power Publications and the Australian Film Commission in 1991 and edited by him. His essay won the 2010 McLaren-Lambart Award for Best Essay from the Society for Animation Studies.